THE USE OF Kaempferia galanga AND Curcuma xanthorrhiza FERMENTED TO IMPROVE THE IMMUNITY OF Oreochromis niloticus AGAINST Streptococcosis - Khairia, Khairia; Syawal, Henni; Luksityowati, Iesje; Riauwaty, Morina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Streptococcus agalactiae is a bacterium that causes streptococcosis, which attacks tilapia. This research was conducted from March to June 2022 at the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, University of Riau. This study aims to understand the best dose of fermented Kaempferia galanga and Curcuma xanthorrhiza, which are added to the feed to increase Oreochromis niloticus immunity. The method used was experimental with a completely randomized design (CRD) with five treatment levels and three replications. The treatments applied were Kn: Negative control (no treatment used), Kp: positive control (no treatment used and infected with S.agalactiae), P1 (100 mL/kg feed), P2 (125 mL/kg feed), P3 (100 mL/kg feed) and infected with S. agalactiae. The fish were contaminated on the 32nd day at a density of bacteria 108 CFU/mL of 0.1 mL/fish intramuscularly, and then the fish were reared up to the 46th day. The results showed that the fermented K.galanga and C.xanthorrhiza affected the haematology of O.niloticus. The best dose was in P3 with a dose of 150 ml/kg of feed which showed total erythrocytes of 2.01 x106 cells/mm3, hematocrit value of 27.33%, a hemoglobin level of 7.93 g/dL, total leukocytes of 6.59 x104 cells/mm3, lymphocytes 77.33%, monocytes 14.00%, neutrophils 8.67%, growth with a weight of 34.06 g, a length of 7.5 cm and a survival rate of 93.33%. Based on the data obtained, it can be concluded that fermented K.galanga and C.xanthorrhiza can increase the immunity of O.niloticus against Streptococcosis disease